Dramatic response to neoadjuvant savolitinib in marginally resectable lung adenocarcinoma with MET exon 14 skipping mutation: A case report and literature review - Tian, Jiangfang; Lin, Zhen; Chen, Yueyun; Fu, Yang; Ding, Zhenyu (Frontiers in Oncology, 2022)
Mesenchymal-epithelial transition (MET) exon 14 skipping mutation (METex14) is a low-frequency driver mutation in metastatic NSCLC (3-4%) and associated with a poor prognosis. With the advent of selective MET inhibitors such as capmatinib, tepotinib, savolitinib, the outcome of these patients was significantly improved. Here we report 76-year-old male with marginally resectable stage IIIB lung adenocarcinoma harboring METex14 was successfully treated with savolitinib for neoadjuvant therapy. Primary tumor was observed 82% shrinkage and only 5% tumor was viable by pathology in the following radical surgery. A dozen of studies tested the efficiency of neoadjuvant immunotherapy or immuochemotherapy, but for NSCLC with driver mutations, neoadjuvant targeted therapy might be more appropriate. We advocated the neoadjuvant MET TKI treatment for NSCLC.